Editorial: Intention in information systems adoption and use: Current state and research directions - Yogesh Dwivedi (International Journal of Information Management, 2023)
Intention has been a key dependent variable in information system (IS) research for the last several decades. It features in various IS acceptance models including the technology acceptance model (TAM), the elaboration likelihood model, the IS success model, and the unified theory of acceptance and use of technology (UTAUT). In the context of IS adoption and use, intention has been portrayed in different forms including intention to adopt, intention to use, intention to continue use, intention to discontinue, and intention to switch. It has been modeled as an antecedent to behavior, a consequent of behavior, and a proxy for behavior. Prior studies of intention have been contextualized in a various settings involving use contexts (i.e., voluntary vs. mandatory use), populations (i.e., non-adopters, adopters, users), respondents (i.e., students, employees), and duration of use (i.e., limited vs. indefinite time), have used cross-sectional and longitudinal empirical designs, and employed different measurement instruments. This editorial provides a brief review of extant IS literature on intention, highlights underlying issues, and proposes directions for future research.